Religió i religiositat en el Tirant lo Blanc. - ESPADALER, ANTON M. (Scripta, 2019)
This paper highlights two ways of explaining the religious matter in the Tirant lo Blanc. One way that hardly agrees with the Church's doctrine, but seems to do so when the practice of chivalry takes form of crusade, meanwhile extending a formal, external and routine experience of Christianity, in spite of its omnipresence; and another one in which the writer tries to respect the articles of Faith and to redirect the behavior of the characters into a less accommodative faith experience, and more concerned with doctrinal requirements.